Frecuencia de brucelosis y posibles factores de riesgo asociados en hatos caprinos del cantón Zapotillo - Ordóñez Benítez, Ramiro Ademir (2023)
Brucellosis is an infectious disease that affects cattle, goats, sheep, swine, and humans. It causes reproductive problems, such as abortions, orchitis, and retained placenta. In this context, in the parish of Zapotillo in the province of Loja, it was proposed to determine the frequency of antibodies against brucellosis in the goats of the sector as well as the risk factors associated with the presence of the disease. For this purpose, a cross-sectional observational design was used in which the Rose Bengal and Competitive Elisa tests were applied to 50 goat blood samples and a survey. The results showed no antibodies against goat brucellosis in the area. Likewise, there were no risk factors associated with the presence of the disease because none of the animals were positive. However, it is necessary to have a sanitary plan that includes the management of this disease to prevent epidemiological events.